Exploration of the Evolution of Flavor Profiles in Ham Sausage during Storage Based on GC-MS, Electronic Nose and Electronic Tongue - Guangbin XIN; Yujuan XU; Cong LI; Zhaoming WANG; Hui ZHOU; Baocai XU (Shipin gongye ke-ji)
This study aimed to comprehensively analyze the changes in flavor characteristics of ham sausage during storage from the perspectives of aroma and taste. The changes in aroma were investigated by gas chromatography-mass spectrometry (GC-MS) and electronic nose (E-nose) combined with the detection of free fatty acids (FFAs), lipid oxidation and protein oxidation. Taste changes were evaluated through electronic tongue (E-tongue) in conjunction with free amino acids (FAAs) detection. Partial least squares discriminant analysis, principal component analysis and correlation analysis were used to explore the correlation and change patterns among these parameters. The results of aroma analysis showed that a total of 19 volatile compounds were identified in ham sausage during storage, and with the increase of storage time, the content of esters decreased significantly (P<0.05), the content of ketones and furans and thiophenes increased significantly (P<0.05), and the content of aldehydes showed a tendency of increasing first and then decreasing. The significant volatile compounds affecting aroma were propyl acetate, 3-methylthiophene, acetone, and 1-methoxy-2-propyl acetate. In addition, the content of FFAs decreased significantly (P<0.05), and the levels of lipid oxidation and protein oxidation increased significantly (P<0.05). The results of taste analysis showed that the umami and glutamate content of ham sausage decreased significantly (P<0.05) with the increase of storage time, and the bitterness and histidine content increased significantly (P<0.05) with the increase of storage time. In conclusion, the changes in aroma characteristics of ham sausage during storage were attributed to lipid oxidation, oxidative degradation of FFAs, protein oxidation, and the interaction between proteins and volatile compounds, and the changes in taste characteristics were mainly caused by the changes in glutamate and histidine content.